2014
DOI: 10.1038/bjc.2014.290
|View full text |Cite
|
Sign up to set email alerts
|

Phase I ficlatuzumab monotherapy or with erlotinib for refractory advanced solid tumours and multiple myeloma

Abstract: Background:Ficlatuzumab, a humanised hepatocyte growth factor (HGF) IgG1κ inhibitory monoclonal antibody, was evaluated for recommended phase II dose (RP2D), safety, pharmacokinetics (PKs), antidrug antibody (ADA), pharmacodynamics (PDs) and antitumour activity as monotherapy or combined with erlotinib.Methods:Patients with solid tumours received ficlatuzumab 2, 5, 10 or 20 mg kg–1 intravenously every 2 weeks (q2w). Additional patients were treated at the RP2D erlotinib.Results:Forty-one patients enrolled at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…However, transcriptional upregulation has been observed resulting from Stat-3 and c-Src expression [60], and the co-expression of HGF and cMET in tumour cells can drive autocrine activation, as well as increased transcription for both genes. A number of studies have identified that HGF expression and autocrine cMET activation decreases sensitivity to cMET inhibitors, and stromal HGF levels have been linked to clinical responses in patients treated with the anti-HGF agent, ficlatuzumab [61][62][63], demonstrating the importance of the use of biomarkers in predicting clinical responses.…”
Section: Mis-regulation Mechanisms Of Hgf/cmetmentioning
confidence: 99%
See 2 more Smart Citations
“…However, transcriptional upregulation has been observed resulting from Stat-3 and c-Src expression [60], and the co-expression of HGF and cMET in tumour cells can drive autocrine activation, as well as increased transcription for both genes. A number of studies have identified that HGF expression and autocrine cMET activation decreases sensitivity to cMET inhibitors, and stromal HGF levels have been linked to clinical responses in patients treated with the anti-HGF agent, ficlatuzumab [61][62][63], demonstrating the importance of the use of biomarkers in predicting clinical responses.…”
Section: Mis-regulation Mechanisms Of Hgf/cmetmentioning
confidence: 99%
“…Both onartuzumab and ficlatuzumab, therapeutic antibodies directed against HGF, stabilise the protein, and cause increases in the serum with treatment [87,61,88]. This enables circulating HGF to be used as a pharmacodynamic marker for these agents, but perhaps not as a catch-all predictive biomarker for selecting patients for HGF/cMET therapies.…”
Section: Circulating Hgfmentioning
confidence: 99%
See 1 more Smart Citation
“…Ficlatuzumab (AV-299) is a potent, high affinity and selective HGF-inhibitory antibody developed to inhibit HGF/MET-driven biological activities (79). A phase II study of ficlatuzumab and erlotinib versus placebo and erlotinib (FOCAL study, NCT02318368) is ongoing to assess the value of combined inhibition in patients with EGFR-mutated, EGFR TKI-naïve advanced NSCLC.…”
Section: Anti-hgf Monoclonal Antibodiesmentioning
confidence: 99%
“…The recommended dose for a Phase II trial was identified as 20 mg/Kg every 14 days. [64] Cabozantinib (XL184) It is an inhibitor of several tyrosine kinases including MET, VEGFR2, RET, TYROL3 and AXL. It has been tested in a syngeneic 5TGM1 mouse model of MM with the primary aim of investigating its activity on bone lesions.…”
Section: Tivantinib (Arq197)mentioning
confidence: 99%